Tata Kelola Desa Wisata Berbasis CHSE di Desa Bakas Kabupaten Klungkung - Hanugerah Kristiono Liestiandre; Lily Dianasari Dewa Ayu Made; Ni Made Tirtawati; Hartanti Woro Susianti; Ida Bagus Putra Negarayana; Ni Luh Nyoman Tri Lilasari; Gede Gian Saputra; Dewa Ayu Nyoman Aridayanti (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2021)
The managers and community leaders of Bakas Village admit that they are not ready to manage their village as a tourism village. Another problem is that good governance has not been established in terms of developing a tourism village and there are several conditions for local communities who are not ready to provide services to tourists who come because there is no clear management system. This community service is carried out in 3 stages with participants from all stakeholders. tourist village. The end result of this community service is to increase public understanding of the CHSE-based tourism village governance system, the formation of a tourism management system managed by a professional management agency in the Bakas Village area that accommodates the aspirations of local communities, and increasing the community's ability to provide excellent service with CHSE-based.